Usefulness of patient education materials for central line associated blood stream infections - Zellmer, Caroline; Zimdars, Peggy; Safdar, Nasia (International Journal of Infection Control, 2016)
Central line associated bloodstream infections (CLABSI) are costly, cause the prolongation of a patient’s hospital stay and are of increasing incidence in the United States. Patient participation, awareness and knowledge of CLABSI are pivotal to prevent the acquisition of these life-threatening infections. We completed a systematic evaluation of materials for patients’ education on CLABSI using a verified tool, the Patient Education Materials Assessment Tool (PEMAT) in order to determine the actionability and understandability of said materials. Patient education materials we found received mediocre scores in both categories.